Inflammatory mechanisms and therapeutic advances in chronic endometritis - Yan, Xinyang; Jiao, Jiao; Wang, Xiuxia (Frontiers in Immunology, 2025)
Chronic endometritis (CE) is a persistent inflammatory disorder of the endometrium, associated with infertility, recurrent pregnancy loss, and implantation failure. Diagnosis primarily depends on hysteroscopy and immunohistochemistry, while microbial dysbiosis and antibiotic resistance pose significant challenges to effective management. The pathogenesis of CE involves microbial infections that induce immune dysregulation through TLR/NLR signaling pathways, metabolic reprogramming of immune cells, miRNA-mediated inflammatory responses, and DNA methylation alterations. The activation of pro-inflammatory mediators and the NLRP3 inflammasome further aggravates endometrial dysfunction. Treatment typically includes oral antibiotics and intrauterine therapies, although their efficacy is variable. Probiotics have demonstrated potential in restoring microbial balance. This review outlines the inflammatory mechanisms underlying CE and recent therapeutic advancements, highlighting potential targets for improving treatment outcomes.